Investigating the influence of gamification on motivation and learning outcomes in online language learning - Shen, Zijun; Lai, Minjie; Wang, Fei (Frontiers in Psychology, 2024)
This study investigates the influence of gamification integration on language learning achievement among Chinese students while probing the mediating role of learners' motivation. Furthermore, it extends the boundaries of this investigation by exploring the moderating effect of digital literacy as a psychological predisposition. Data is collected through surveys from Chinese students enrolled in linguistic programs, employing a stratified random sampling technique and analyzed via SmartPLS SEM. The findings affirm the significant and positive impact of gamification integration on language learning achievement. The study introduces a moderated mediation model where learners' motivation serves as the mediator, and digital literacy acts as a moderator, further accentuating the significant impact of this integrated approach. This research advances our theoretical understanding of language learning, validating gamification's effectiveness as a motivational tool, and introduces digital literacy as a critical factor, providing deeper insights into personalized language learning experiences.